Motivation of Private High School Fresh Graduated Students on Batam in Choosing the Accounting Education - Irsutami Irsutami; Muhammad Fikri (Journal of Applied Accounting and Taxation, 2016)
The purpose of this research is to investigate how vocational high school graduated students on Batam are motivated in terms of choosing the accounting education in a university. Variables that are used on this research are social and economic background, career factor and cost factor toward motivation of vocational high school graduated students on Batam in terms of choosing accounting education in a university. Population in this research is all students on vocational high schools and private high schools on Batam. There are 354 vocational high school and private high schools students on Batam.The results of this research indicates that social and economic background factor has positive impact on graduated students’ motivation, career factor has positive impact on graduated students’ motivation, and cost factor also has positive impact on graduated students’ motivation in terms of choosing the accounting education in a university.